SURAH YASIN DALAM TAFSIR AL-IBRIZ - Siti Rosida (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
Surah Yasin is surah which often read and popular among Islamic societies. That is because of many hadith narrated about the primacy. But not only read it, knowing the meaning contained in it is also very important. This research uses qualitative method. The data which are found then analyzed using the theory tafsir maudu‘i. Surah Yasin in the Tafsir al-Ibriz has a different explanation than the other surah, namely khatimah surah and picture. Bisri Mustafa classifies surah Yasin into three principals, that is about the oneness of Allah, provision treatise, and the day of resurrection (yaum al-Ba‘ath) and the day gathered all beings (yaum al-Hashr).